In vitro anti-Bacterial and Biological properties of magnetron sputtered silver nanoparticles containing titanium implants - D. Raja rajan; C. Ramani; M. Balasubramani; K. Nagarajan; Balakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Bacterial infection followed by implant fixation is a common complication after surgery. In order to reduce the incidence of implant-associated infections, several biomaterial surface treatments have been proposed. In this study, the effect of in vitro antibacterial activity of magnetron sputtered silver nanoparticles was studied. Sputtering was done using radiofrequency magnetron sputtering technology. Film applicator coating assay was used to assess the antibacterial effect of the coated titanium implants. SEM examination revealed successful deposition of silver nanoparticles on the titanium surface. The average diameter of the nanoparticles was 40-60 nm. SEM examination before incubation and after incubation of bacteria was done. The bactericidal ratio between the uncoated and coated implant was determined.